The pleistocene-holocene transition in Southwestern France: A focus on the laborian. (30th October 2020) - Langlais, Mathieu; Chevallier, Aude; Fat Cheung, Célia; Jacquier, Jérémie; Marquebielle, Benjamin; Naudinot, Nicolas
Abstract: During the Pleistocene-Holocene transition, the European archaeological records can be divided into two broad entities – the Epigravettian in the northern Mediterranean Basin and the industries characterized by the return of a well-developed blade technology in northwestern Europe. This large Western European techno-complex comprises several cultural traditions defined essentially by various types of projectile points. One of these cultures, the Laborian, occupies an area at the crossing of northern traditions (Ahrensbourgian) and the Epigravettian techno-complex. Situated between the Azilian and the Mesolithic, the Laborian (ca 12.5–11 Ka cal. BP) is, paradoxically, poorly defined in southwestern France where it was initially defined. In fact, data for this culture is essentially available in the surrounding regions and especially in northern and western France. Revaluation of key Laborian lithic assemblages as well as the discovery of new sites today allow to draw a new picture of the various cultural traditions occupying this large area around 12 Ka cal. BP. Despite the scarcity of data on hunted fauna, we can observe the dominance of the exploitation of large game typical of open temperate landscapes. Osseous industry is also rare but we note the maintenance of bone barbed points in few sites. Artistic. conventions (engraved pebbles or bones) show several symbolic innovations, such as the development of a unique zoomorphic art. Lithic hunting weaponry essentially based around pointed elements, much like during the Azilian, allows to highlight two chronological phases along the Laborian culture: an older phase with straight backed points with truncated bases (Malaurie points) and bitruncated backed blades ("rectangles") and a recent phase with pointed backed bladelets (Blanchères points) and bitruncated trapezoids. The production of large, standardized, straight blades with flat cross-sections during the Laborian reveals clear similarities with concepts recognized in Belloisian collections from Northern France even if blade lengths rarely reach the standards known on these sites. Finally, the technological study of domestic stone tools and hunting weaponry is an effective means for reconstructing larger scale evolution processes influencing these last Pleistocene societies and the persistence of their traditions into the European Mesolithic.